Finding 10% hidden electricity in crystalline Si solar cells using PDMS coating and three‐dimensional cell arrays. (30th January 2020) - Yun, Min Ju; Sim, Yeon Hyang; Cha, Seung I.; Lee, Dong Yoon
Abstract: Over the decades, solar cells have been developed to achieve higher energy conversion efficiency. However, the fabrication of modules has resulted in electricity production loss, but this has not attracted as much attention as the solar cells. As a result, the improved performance of solar cells has not been fully revealed at the panel scale. Furthermore, the standard testing conditions, such as 1 sun, AM1.5, which is very strong incident light, does not fully reflect the electricity production capabilities of solar panels because of performance degradation under oblique and weak illumination. Simple modification of the module fabrication process, including poly‐dimethylsiloxane (PDMS) coatings and three‐dimensional (3‐D) structured modules by one‐directional angled arrays of each cell, has revealed 13.4% extra hidden electricity in solar panels with some types of crystalline silicon (Si)‐based solar cells through high transmission to short wavelength light, recapture of the light reflected from Si solar cell surface textures by the PDMS coating and enhanced power production under oblique incident light or scattered light through a 3‐D module. Further studies to find hidden electricity should be followed by the development of solar cell device structures to improve electricity production, rather than being restricted to optimizing energy conversion efficiency. Abstract : Utilization of poly‐dimethylsiloxane (PDMS) coatings and three‐dimensional (3‐D) structured modules by one‐directional angled arrays of each cell, revealed 13.4% extra hidden electricity in solar panels of crystalline silicon (Si)‐solar cells through high transmission to short wavelength light, recapture of the light reflected from Si solar cell surface textures by the PDMS coating and enhanced power production under oblique incident light through a 3‐D module.